PENGARUH PELATIHAN DAN PELUANG KARIR TERHADAP MOTIVASI KERJA KARYAWAN DI KANTOR PUSAT KSP CU USAHA KITA KABUPATEN SEKADAU - magdalena, lin; Winanda Putri, Della (FOKUS : Publikasi Ilmiah untuk Mahasiswa, Staf Pengajar dan Alumni Universitas Kapuas Sintang., 2025)
This study aims to determine and analyze the influence of training and career opportunities on employee work motivation at the Head Office of KSP CU Usaha Kita in Sekadau Regency. Data collection was conducted using questionnaires. The population consisted of employees at the Head Office of KSP CU Usaha Kita in Sekadau Regency. The sample size was 28 respondents. The analysis used was multiple linear regression assisted by SPSS version 26. The results of the study, based on validity and reliability tests, indicated that all items were valid and reliable. The multiple linear regression model to predict the variables of training (X1) and career opportunities (X2) affecting the work motivation variable (Y) is formulated as follows: Y = -0.544 + 0.334 X1 + 0.682 X2. The obtained probability value (sig F change) and Pearson's correlation coefficient were 0.756 and 0.856, respectively. The correlation table shows that the relationships between variables X1, X2, and Y are in the strong category. The t-test results show significance levels of 0.021 and 0.000, both less than 0.050. The hypothesis of this study is that training (X1) and career opportunities (X2) have a significant effect on work motivation (Y). The F-test results with a significance level of 0.000 < 0.05 indicate that training and career opportunities significantly influence work motivation (Y). The coefficient of determination results show a value of 78.5%.